2008
DOI: 10.1007/s00248-008-9448-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Microbiota Along the Digestive Tract of Juvenile Atlantic Salmon (Salmo salar L.)

Abstract: Dominant bacterial microbiota of the gut of juvenile farmed Atlantic salmon was investigated using a combination of molecular approaches. Bacterial community composition from the stomach, the pyloric caeca, and the intestine was assessed by extracting DNA directly from each gut compartment. Temporal temperature gradient gel electrophoresis (TTGE) analysis of 16S ribosomal DNA (rDNA) amplicons showed very similar bacterial compositions throughout the digestive tract. Band sequencing revealed a narrow diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
139
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(159 citation statements)
references
References 42 publications
16
139
0
4
Order By: Relevance
“…The TVCs in the stomach are lower than those revealed by Wu et al (2010) from the intestine. This result is congruent with Molinari et al (2003) and Navarrete et al (2009), who derived their conclusion from Nile tilapia Oreochromis niloticus and Atlantic salmon Salmo salar, respectively. As plate counts can only disclose the cultivable aerobic and facultative anaerobic bacteria, a culture-independent method, 16S rDNA clone library technique, is used to present the total microbiota in the stomach.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The TVCs in the stomach are lower than those revealed by Wu et al (2010) from the intestine. This result is congruent with Molinari et al (2003) and Navarrete et al (2009), who derived their conclusion from Nile tilapia Oreochromis niloticus and Atlantic salmon Salmo salar, respectively. As plate counts can only disclose the cultivable aerobic and facultative anaerobic bacteria, a culture-independent method, 16S rDNA clone library technique, is used to present the total microbiota in the stomach.…”
Section: Discussionsupporting
confidence: 92%
“…Molinari et al (2003) recorded higher viable bacteria in both the anterior and the posterior gut than in the stomach of semi-intensively cultured Oreochromis niloticus. Navarrete et al (2009) reported the average bacterial density to be 1 9 10 7 and 5 9 10 7 bacteria g -1 in the stomach and intestine, respectively, in Salmo salar using epifluorescence microscopy. Zhou et al (2009) disclosed the difference in bacterial composition in the stomach and intestine of adult yellow grouper (Epinephelus awoara), where Empedobacter sp.…”
Section: Introductionmentioning
confidence: 99%
“…Our 16S rRNA clone library sequences identified members of the g-Proteobacteria and Fusobacteria classes as common members of the gut microbiota in adult zebrafish raised in different locations as well as in other fish species (Figure 2). The nature of our study required that we limited our UniFrac analysis to those fish species for which complete (that is, nondereplicated) 16S rRNA clone libraries were available (Table 1), however, these same bacterial classes have been also observed in the intestinal microbiotas of other teleost fishes in culture-independent and culture-based surveys (Huber et al, 2004;Romero and Navarrete, 2006;Kim et al, 2007;Tsuchiya et al, 2008;Merrifield et al, 2009;Navarrete et al, 2009Navarrete et al, , 2010. This suggests that these specific bacterial groups are especially well adapted for the environment within the fish intestine, despite large evolutionary and geographic distances between their fish hosts.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be attributed to the incomplete larvae development of the four fish species, which influences the composition of the intestinal microbiota. Denaturing gradient gel electrophoresis of the 16S rRNA gene has been successfully used to characterize bacterial populations associated with fish larvae (Jensen et al, 2004;Brunvold et al, 2007;Navarrete et al, 2009). Indeed, the banding patterns can re ect the composition of the dominant bacterial community.…”
Section: Discussionmentioning
confidence: 99%
“…In fish intestine, these microbiota are dominated by four bacterial phyla, Proteobacteria, Fusobacterium, Actinobacteria, and Cyanobacteria, but different hosts harbor distinct species and strains (Ley et al, 2006). Species and other factors affecting intestinal community structure, such as diet, age, and environmental factors have been examined (Austin, 2006;Kim et al, 2007;Navarrete et al, 2009;Ward et al, 2009).…”
Section: Introductionmentioning
confidence: 99%